1996
DOI: 10.1071/ea9960533
|View full text |Cite
|
Sign up to set email alerts
|

Plant population dynamics in subterranean clover and murex medic swards. 3. Effect of pod burial, summer grazing and autumn cultivation on emergence

Abstract: Murex medic (Medicago murex Willd.) seedling recruitment is more sensitive to soil water at the time of emergence than subterranean clover (Trifolium subterraneum L.). Murex medic pods normally lay on the soil surface. Shallow burial of pods may be beneficial when soil moisture is marginal for germination and emergence. In addition, the tightly coiled structure of murex medic pods may also act as a barrier to water uptake by the seed. Two methods of burying murex medic pods were investigated in the field: (i) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…In the free grazing area, due to the influence of grazing livestock, the seeds of Leymus chinensis with smaller seeds are more likely to be buried, so there will be a higher germination rate. This scenario is more consistent with the research results of Blumenthal and Ison (1996) [41]. However, in terms of the trade-off between sexual reproduction and asexual reproduction, although Qing (2002)'s research results in 1999 showed that the seed-bearing percentage in the free-grazing area was much higher than that in the enclosed area and that the ratio of healthy seeds to reproductive branches was also higher in the free-grazing area than that in the enclosed area, the number of ears in the enclosed area was lower than that in the free-grazing area.…”
Section: Effect Of Grazing On Seed Source Of Germinating Seed Bank Of...supporting
confidence: 93%
“…In the free grazing area, due to the influence of grazing livestock, the seeds of Leymus chinensis with smaller seeds are more likely to be buried, so there will be a higher germination rate. This scenario is more consistent with the research results of Blumenthal and Ison (1996) [41]. However, in terms of the trade-off between sexual reproduction and asexual reproduction, although Qing (2002)'s research results in 1999 showed that the seed-bearing percentage in the free-grazing area was much higher than that in the enclosed area and that the ratio of healthy seeds to reproductive branches was also higher in the free-grazing area than that in the enclosed area, the number of ears in the enclosed area was lower than that in the free-grazing area.…”
Section: Effect Of Grazing On Seed Source Of Germinating Seed Bank Of...supporting
confidence: 93%
“…Defoliation also promotes tillering of grasses (Hodgson 1990), stimulates the regrowth of herbage (Leriche et al 2001) and indirectly impacts on underground parts of plants and soil properties (Ford & Grace 1998;Greenwood & Hutchinson 1998). Treading by livestock buries herbage seed and thereby promotes imbibition and germination of seed (Blumenthal & Ison 1996). Treading also fragments plant litter and therefore accelerates its decomposition (Zacheis et al 2001).…”
Section: Comparative Environmental Impact Of Defoliation and Treadingmentioning
confidence: 99%
“…Siles et al (2016) have shown that the effect of burial is species-specific. Blumenthal & Ison (1996) found that marginal humidity conditions in the shallow sowing of pods of Medicago murex could be beneficial for the germination and emergence of seedlings, and that this effect may vary in terms of the environmental stress to which seeds are subjected. Our study shows that the effect of burial varies in terms of the species and pod traits (i.e.…”
Section: Discussionmentioning
confidence: 99%